2019
DOI: 10.14710/jitaa.44.3.277-285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zeolite inclusion in aflatoxin B1-contaminated diet on the performance of laying duck

Abstract: The researchwas objected to study the effect of zeolite inclusion in aflatoxin B1 (AFB1) contaminated diet on the performance of laying duck. A completely randomized design was adopted in the in vivo experiment that consisted of 4 treatments, namely: (1) commercial feed (Control); (2) AFB1-contaminated feed 70 ppb (AFC); (3) Control + 2% zeolite; and (4) AFC + 2% zeolite. Each treatment had 4 replications with 4 ducks in each replication. A total of 64 eight months-female Alabio duck (Anas platyrinchos Borneo)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Body weight and carcass weight were also lower in ducks receiving zeolite. Other researchers [ 29 ] investigated the effect of 2% of zeolite in the diet of laying ducks and reported a greater body weight in these birds, which again implies that the excessive supplementation of zeolite may have a negative effect on the body weight of birds. Chung and Choi [ 30 ] demonstrated that a diet with a 2% inclusion of bentonite had no effect on the body weight of ducks, but a higher feed conversion ratio was reported, similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Body weight and carcass weight were also lower in ducks receiving zeolite. Other researchers [ 29 ] investigated the effect of 2% of zeolite in the diet of laying ducks and reported a greater body weight in these birds, which again implies that the excessive supplementation of zeolite may have a negative effect on the body weight of birds. Chung and Choi [ 30 ] demonstrated that a diet with a 2% inclusion of bentonite had no effect on the body weight of ducks, but a higher feed conversion ratio was reported, similar to our study.…”
Section: Discussionmentioning
confidence: 99%